GTL-1, a Calcium Activated TRPM Channel, Enhances Nociception - Cohen, Emiliano; Kumar, Rakesh; Zinger, Tal; Priel, Avi; Treinin, Millet (Frontiers in Pharmacology, 2020)
C. elegans PVD neurons are conserved for morphology, function and molecular determinants with mammalian polymodal nociceptors. Functions of polymodal nociceptors require activities of multiple ion channels and receptors including members of the TRP family. GTL-1, a member of the TRPM subclass of TRP channels, was previously shown to amplify PVD-mediated responses to optogenetic stimuli. Here we characterize effects of GTL-1 on PVD-mediated behavioral responses to noxious stimuli. We show that GTL-1 is required within PVD for the immediate and enduring response to thermal (cold) stimuli. But, find no significant reduction in percent animals responding to single or to repeated noxious mechanical stimuli. Nevertheless, PVD specific knockdown of gtl-1expression reduces the magnitude of responses to noxious mechanical stimuli. To understand GTL-1’s mechanism of action we expressed it in HEK293 cells. Our results show GTL-1-dependent currents induced by activation of a Gαq-coupled Designer Receptor Exclusively Activated by Designer Drugs (DREADD). In addition, using excised patches we show that GTL-1 can be activated by internal calcium. Our results are consistent with indirect, calcium dependent, activation of GTL-1 by noxious stimuli. This mechanism explains the GTL-1-dependent amplification of responses to multiple stimuli optogenetic and sensory in PVD.